2014
DOI: 10.1021/ic501604c
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism of (001) Oriented Perovskite SrTiO3 Microplatelets Synthesized by Topochemical Microcrystal Conversion

Abstract: To develop a better understanding of the mechanism responsible for topochemical microcrystal conversion (TMC) from Aurivillius SrBi4Ti4O15 precursors to perovskite SrTiO3 microplatelets, compositional/structural evolutions, morphological development, and reaction interface evolution of the (001) oriented SrBi4Ti4O15 microplatelets were investigated during the conversion process. The results show that multiple topotactic nucleation events of SrTiO3 occurred directly on the surfaces of SrBi4Ti4O15 above 700 °C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 42 publications
(63 reference statements)
0
24
0
1
Order By: Relevance
“…Since particles with a plate shape are easier to assemble on the water/oil interface, 34 how to synthesize plate-like particles becomes a signicant issue for the assembly of particles into a lm using an interface strategy. Recently a topochemical conversion method has been applied to the greatest extent in other perovskite systems, such as BaTiO 3 , 38 Na 0.5 Bi 0.5 TiO 3 , 39 SrTiO 3 , 40,41 PbTiO 3 . 42 These kinds of particles with a highaspect ratio and special orientation would provide excellent templates for the preparation of preferred orientation relevant perovskite ferroelectrics, and the other key issue is how to assemble these templates to form preferred orientation structures.…”
Section: Introductionmentioning
confidence: 99%
“…Since particles with a plate shape are easier to assemble on the water/oil interface, 34 how to synthesize plate-like particles becomes a signicant issue for the assembly of particles into a lm using an interface strategy. Recently a topochemical conversion method has been applied to the greatest extent in other perovskite systems, such as BaTiO 3 , 38 Na 0.5 Bi 0.5 TiO 3 , 39 SrTiO 3 , 40,41 PbTiO 3 . 42 These kinds of particles with a highaspect ratio and special orientation would provide excellent templates for the preparation of preferred orientation relevant perovskite ferroelectrics, and the other key issue is how to assemble these templates to form preferred orientation structures.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20] In TGG or RTGG, aligned template particles are used to direct oriented grain growth within a dense, fine-grained ceramic matrix. 21 Recently, several published reports have demonstrated that highly [001] textured PMN-PT binary ceramics exhibit substantially enhanced piezoelectric coefficient and high electromechanical coupling factor. [22][23][24][25][26][27][28] Thus, it is expected that [001] oriented PIN-PMN-PT ternary ceramics would exhibit high and much more stable electrical performance as compared to binary PMN-PT textured ceramics.…”
mentioning
confidence: 99%
“…Based on the previous literature, it can be found that the hydrothermal topotactic epitaxy of titanate was an effective strategy for the controllable synthesis of SrTiO 3 mesocrystals. 104,105 For instance, Majima and coworkers have prepared a novel perovskite SrTiO 3 mesocrystal superstructure with well-dened orientation of assembled cubic nanocrystals induced by topotactic epitaxy from TiO 2 mesocrystals through a facile hydrothermal treatment. 105 In this case, starting from sheet-like TiO 2 mesocrystals, which consisted of assembled anatase TiO 2 nanocrystals with dominant (001) facets, Sr 2+ ions from Sr(OH) 2 reacted with TiO 2 in an alkaline solution to generate an epitaxial overlayer of SrTiO 3 grains at the interface via the dissolution-precipitation process.…”
Section: Bazro 3 Mesocrystalsmentioning
confidence: 99%